2021
DOI: 10.1097/qad.0000000000002722
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a community-wide combination HIV prevention intervention on knowledge of HIV status among adolescents

Abstract: Objective: To determine the impact of a community-wide combination HIV-prevention package (PopART Intervention) that includes universal testing and treatment (UTT) on knowledge of HIV status, among adolescents aged 15--19 years. Design: The HPTN 071 (PopART) for Youth (P-ART-Y) study was nested within HPTN 071 (PopART), a three-arm, cluster-randomized trial conducted from 2013 through 2018 in 21 communities in Zambia and South Africa. Communities were randomly assigned to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…We found that advanced HIV disease [WHO stage III/IV] and management in a large HIV care center were associated with higher risk of attrition. Regarding age, it has been previously shown that adolescents are a group at risk for poor outcomes [40][41][42] and that adolescent-friendly screening interventions are needed to increase adolescents' access to ART programs [43][44][45]. We observed similar results in the univariate models but the impact of age was lost in the multivariate analysis.…”
Section: Plos Global Public Healthsupporting
confidence: 73%
“…We found that advanced HIV disease [WHO stage III/IV] and management in a large HIV care center were associated with higher risk of attrition. Regarding age, it has been previously shown that adolescents are a group at risk for poor outcomes [40][41][42] and that adolescent-friendly screening interventions are needed to increase adolescents' access to ART programs [43][44][45]. We observed similar results in the univariate models but the impact of age was lost in the multivariate analysis.…”
Section: Plos Global Public Healthsupporting
confidence: 73%
“…Adaptation, defined as a “process of making modifications or changes to the design or implementation of an intervention”, is important for optimizing implementation [ 10 , 11 ]. Adaptations are important for meeting a specific target group needs or as a response to a contextual stimulant, such as disease outbreaks [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PopART for Youth (P-ART-Y) study aimed to determine the acceptability and uptake of HIV testing among adolescents and young adults aged 10-24 years (young people) and was implemented from October 2015 to December 2017, the main findings from the study have been published elsewhere (13,18,19). The P-ART-Y study was nested within the HPTN071 (PopART) trial, a three-arm cluster-randomized trial conducted in 12 communities in Zambia and nine communities in South Africa which was implemented from November 2013 to December 2017 (13).…”
Section: Trial Design and Settingmentioning
confidence: 99%
“…In Africa, HIV/AIDS is now the leading cause of death among adolescents, notably among girls, and is ranked second globally next to unintentional injuries (1,2). Furthermore, an estimated 250,000 adolescents aged [15][16][17][18][19] become newly HIV-positive annually (3). Compared to adults, older adolescents, and children/infants, little is known about the burden of HIV and AIDS among young adolescents (aged 10-14 years) as data on them are rarely collected, and the statistics that are reported aggregate them with older youth.…”
Section: Introductionmentioning
confidence: 99%